Analisis Optimalisasi Benefit Aset Keuangan Nelayan Ubur-Ubur dalam Mewujudkan Kesejahteraan - Rahayu, Sri; Diatmika, I Putu Gede (Universitas Pendidikan Ganesha, 2021)
The appearance of Jellyfish on Teluk Saleh Island, Sumbawa Regency, is an opportunity to develop this product, not only exporting raw materials, but also in the form of processed materials so that they have a greater added value than just raw materials. The purpose of this study is to analyze the optimization of the business benefits of Jellyfish fishermen in realizing prosperity. This type of research is descriptive research with survey methods through a qualitative approach. The data analysis technique is through data reduction, data presentation and conclusion drawing. A large number of fishermen have benefited from the business of catching jellyfish on the island of Teluk Saleh. Utilization of Jellyfish in Saleh Bay can have a positive impact because it is considered a stinging pest and can become Saleh Bay's export commodity which has a high selling value and price. feel self-sufficient and have implications for improving the welfare of Jellyfish fishermen in Teluk Saleh.